ANALISIS PENGARUH MANAJEMEN RISIKO DAN MANAJEMEN KINERJA TERHADAP ISLAMICITY PERFORMANCE INDEX PERBANKAN SYARIAH TAHUN 2010--2022 - Khoiri, Abdul; Trihantana, Rully; Fauziah, Ratu Dinny (SAHID BANKING JOURNAL, 2024)
This study aims to determine the effect of risk management and performance management on the Islamicity performance index. Islamicity performance index measurement uses Profit Sharing Ratio, Zakat Performance Ratio, and, Islamic income vs. non-Islamic income, while risk management uses Non Performing Financing/NPF and Finance to Deposit Ratio/FDR measurements and performance management uses Return On Asset/ROA measurements. This type of research is associative research with a quantitative approach. The sampling technique in this study used purposive sampling and cross section methods from 2010 to 2022 in order to obtain 7 Islamic Commercial Banks that met the criteria. Analysis of the data used to test the hypothesis using SPSS version 26. The results of the study show that non-performing financing has effect on the Profit Sharing Ratio, Financing to Deposit Ratio has effect on the Profit Sharing Ratio, and Return On Assets has effect on the Profit Sharing Ratio. Non-performing financing has no effect on the Zakat Performance Ratio, Financing to Deposit Ratio has no effect on the Zakat Performance Ratio, and Return On Assets has an effect on the Zakat Performance Ratio. Non-performing financing has no effect on Islamic income vs non-Islamic income, financing to deposite ratio has no effect on Islamic income vs non-Islamic income, and Return On Assets has an effect on Islamic income vs non-Islamic income.